Productivity and Biomass Properties of Poplar Clones Managed in Short-Rotation Culture as a Potential Fuelwood Source in Georgia - Marzena Niemczyk; Margalita Bachilava; Marek Wróbel; Marcin Jewiarz; Giorgi Kavtaradze; Nani Goginashvili (Energies, 2021)
Georgian forests are very valuable natural resources, but due to the lack of affordable alternatives to firewood, people are forced to use forest resources illegally and unsustainably. The aim of this study was to determine the productivity and biomass properties of four poplar clones from Aigeiros and Tacamahaca and one control clone, considering their wood and bark characteristics and their proportion in the stems. Short-rotation woody crops with these clones represent a potential source of commercial fuelwood production in Georgia as an alternative to natural forests. These tree characteristics were evaluated after three years of growth. The survival of the clones was generally high. No significant differences in biomass production (dry matter, DM) were found among the four clones tested (DM of approximately 4 Mg ha−1 yr−1), while the control clone achieved significantly lower values for DM. The biomass specific density was exceptionally high, at 481–588 kg m−3, which was a result of the high proportion of bark mass in the stem (23.3–37.7%), with a density almost twice that of wood. On the other hand, the tested clones had a very high ash content in the biomass (2.6–4.5%), which negatively affected their energy potential expressed as a lower heating value (17,642–17,849 J g−1). Our preliminary results indicated that both the quantity and quality of biomass are important factors to justify the investment in an intensive poplar culture. The four clones should be further considered for commercial biomass production and tested at different sites in Georgia to evaluate the genotype-by-environment interactions and identify the site conditions required to justify such an investment.